Long-term exposure to air pollution and liver fibrosis in the elderly with MASLD - Yanqi Lan; Haixia Zhang; Ahua Wu; Jiankang Huang; Zhinan Guo; Youlan Chen (Scientific Reports)
Abstract This study aimed to investigate the relationship between air pollutants (AP) and liver fibrosis in the older Chinese population with metabolic dysfunction-associated steatotic liver disease (MASLD). A total of 23,887 MASLD subjects aged ≥ 65 years were enrolled in this study. The annual average levels of various APs, including NO2, SO2, O3, CO, and PM, were collected. Logistic regression analysis was conducted to examine the associations between APs and the prevalence of liver fibrosis. The quantile g-computation model was employed to assess the combined effect of the AP mixture. After adjustment for possible confounders, the odds ratios of liver fibrosis at the highest quartile of O3, CO, SO2, PM2.5, and PM10 were 1.50 (1.30, 1.74), 1.26 (1.09, 1.46), 1.22 (1.06, 1.40), 1.49 (1.28, 1.74), and 1.83 (1.56, 2.13) compared to the lowest quartile, respectively. Stratified analysis showed that the effects of APs were more prominent among the males, participants who exercise inactively, those without obesity, and non-diabetic participants (P for interaction < 0.05). The overall AP mixture was positively associated with liver fibrosis, and PM10 mainly contributed to the positive association with liver fibrosis.